RELATIONSHIP BETWEEN THE SIZE OF MACROCYSTS OF SARCOCYSISTIS AUCHENIAE AND ITS VIABILITY IN CANIS FAMILIARIS - Cornejo B., Rossmery (2007)
The objective of the study was to determine weather the size of Sarcocystis aucheniae macrocysts affect its viability and biotic potential in domestic canines. A total of 26 crossbred puppies, 2.5 month of age, 2.6 kg of body weight, were used. Puppies were dewormed and fed with a diet extent of meat. Macrocysts of S. aucheniae were obtained from alpaca and llama´s neck in the local slaughterhouse. Cysts were classified according to size in large (>5 mm) and small (1-3 mm) cysts. Ten puppies were orally infected with 500 large macrocysts (MG) and 12 puppies with 500 small macrocysts (MP), for 2 consecutive days, whereas 6 puppies were kept as controls. Fecal samples were daily collected and analyzed by the flotation method using the Sheather solution to determine the presence of oocysts and sporocysts of Sarcocystis sp. and the modified Stoll method to quantify the number of sporocysts per gram of feces. The results showed that the burden of sporocysts was 3.6 times more in puppies infected with MP than in those infected with MG. Furthermore, the average prepatent period was 16.5 and 11.5 days for MG and MP respectively.